Face of man perspectives on the economic, social, cultural and political development of the Caribbean : the Dr Eric Williams Memorial Lectures 1983-1992 - Lewis, W. Arthur...[et al] (Central Bank of Trinidad and Tobago Port of SpainTT, 1994)
Presents the first ten lectures in the Dr. Eric Williams Memorial Lectures Series. Includes lectures drawn from different disciplines which together cover a broad range of issues that are of particular relevance to the economic , social, cultural and political development of Trinidad and Tobago and the Caribbean region.